Service Gap of Selected Public and Private Commercial Banks in Bangladesh - Akhter , Mst. Momena (i-Proclaim, 2012)
The economy of a country is largely dependent on banking sector. In this case, Bangladesh is not exceptional. Both public and private banks play a vital role in the economy, making up one of the biggest providers of services in the Bangladesh economy. In the current banking environment, service quality is one of the main weapons, which enables the banks to differentiate from each other. It is said that service quality has become an important factor to survive and succeed in the banking sector.  Hence, providing a better service quality is vital, as banks have to compete for customers. In this paper, the factors leading to the service provider gaps in case of selected public and private commercial banks have been identified and measured and it attempts to show the relationship between the provider gaps of these banks and the gap between expected service and perceived service (customer gaps). Two public commercial banks (Janata Bank Ltd., and Agrani Bank Ltd.) and two private commercial banks (Dutch Bangla Bank Ltd., and Prime Bank Ltd.) were selected for the purpose of the study. In this paper there is an endeavor to recognize whether the service provider gaps and the customer gaps are correlated and takes into consideration the problems of organizational quality gaps where the quality losses occur. This will help the management of these banks to know where the service gaps lie and how to close the gaps for providing quality service to their clients. This study shows that the overall service gap is higher in the public commercial banks in comparison to the private commercial banks. To remove this gap and to improve the overall service quality this paper has recommended some measures for both public and private commercial banks in Bangladesh. GEL Classification Code: M30; M31